1958
DOI: 10.1002/jlac.19586160109
|View full text |Cite
|
Sign up to set email alerts
|

Über den Mechanismus der Schiffschen Reaktion

Abstract: Die Kinetik der ScHIFFschen Aldehydreaktion wurde ausfuhrlich mit Formaldehyd und orientierend mit anderen Aldehyden untersucht. Die Versuche sprechen daftir, daD sich zuerst zwei Aminogruppen des Fuchsins mit dem Aldehyd und schwefliger Saure in einem Mechanismus verbinden, der dern der MANNICH-Reaktion ahnelt, worauf Abdissoziation von schwefliger Saure vom zentralen C-Atom und Bildung eines farbigen mesomeren Kations erfolgt. Die Konstante des Dissoziationsgleichgewichtes wurde gernessen. Steigerung der SOZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

1969
1969
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 10 publications
3
11
0
Order By: Relevance
“…The 'Hmr spectrum in DMSO-ti, of material prepared by this method, however. indicates that the correct structure is 14: The spectral evidence leaves no doubt that this complex is a 1 : 1 adduct of structure 14 in agreement with more recent formulations of the coloured Schiff product as an a-aminosulfonic acid (9,11). However, Wieland and Scheuing state that the actual dye is a 2: 1 (aldehyde-pararosaniline) adduct (7) and Hoi-mann et al have found that the colour developed is proportional to the square of the acetaldehyde concentration (9).…”
Section: Scl~iff Reagent Acetaldehyde Addition Productsupporting
confidence: 86%
See 4 more Smart Citations
“…The 'Hmr spectrum in DMSO-ti, of material prepared by this method, however. indicates that the correct structure is 14: The spectral evidence leaves no doubt that this complex is a 1 : 1 adduct of structure 14 in agreement with more recent formulations of the coloured Schiff product as an a-aminosulfonic acid (9,11). However, Wieland and Scheuing state that the actual dye is a 2: 1 (aldehyde-pararosaniline) adduct (7) and Hoi-mann et al have found that the colour developed is proportional to the square of the acetaldehyde concentration (9).…”
Section: Scl~iff Reagent Acetaldehyde Addition Productsupporting
confidence: 86%
“…indicates that the correct structure is 14: The spectral evidence leaves no doubt that this complex is a 1 : 1 adduct of structure 14 in agreement with more recent formulations of the coloured Schiff product as an a-aminosulfonic acid (9,11). However, Wieland and Scheuing state that the actual dye is a 2: 1 (aldehyde-pararosaniline) adduct (7) and Hoi-mann et al have found that the colour developed is proportional to the square of the acetaldehyde concentration (9). For the usual 4.5 x lop3 M pararosaniline hydrochloride concentration and acetaldehyde at 4 x lop4 M the statistical distribution of products (assuming all three amino groups are equally reactive) would be 91.4% unsubstituted, 8.4% monosubstituted, 0.26% disubstituted, and negligible trisubstituted.…”
Section: Scl~iff Reagent Acetaldehyde Addition Productsupporting
confidence: 86%
See 3 more Smart Citations